Editor's Choice – The Impact of Endovascular Aneurysm Repair on Long Term Renal Function Based on Hard Renal Outcomes. (September 2019) - Charles, Edmund R.; Lui, Dennis; Delf, Jonathan; Sayers, Robert D.; Bown, Matthew J.; Sidloff, David; Saratzis, Athanasios
Abstract : Introduction: Over the short term endovascular aneurysm repair (EVAR) is associated with superior outcomes compared with open repair; however, the progression of renal function after EVAR remains unknown because of the use of inconsistent reporting measures. The aim was to define long term renal decline following elective EVAR using estimated glomerular filtration rate (eGFR). Methods: The prospectively maintained in house database was used to identify consecutive patients having elective EVAR who had been followed up for more than five years. Overall, 275 patients (23 females, 8%; mean age, 75 years) who were not previously on renal replacement therapy (RRT) were included (January 2000 to July 2010). Pre-operative, post-operative, and most recent eGFR values were evaluated using the chronic kidney disease epidemiology collaboration equation. The primary outcome was change in eGFR at latest follow up. Results: Patients were followed up over a median of 9 years (range 5–17 years). Their mean eGFR dropped from a pre-operative value of 67 mL/min/1.73 m 2 (standard deviation [SD]: 9.4) to 52 mL/min/1.73 m 2 (SD 7.7), which amounts to a yearly loss of 1.7 units; six patients (2%) required RRT (dialysis) during late follow up. Patients requiring RRT and those with an eGFR loss exceeding 20% at latest follow up compared with baseline were more likely to die during late follow up (odds ratio 2.4 and 3.3 respectively, p < .001). Conclusion: This analysis, with some of the longest available follow up to date, suggests that patients undergoing EVAR may experience a significant long term decrease in renal function. This needs to be taken into account when offering EVAR in younger patients; renal follow up and preservation should be optimised in this patient group.